Risiko Politik Dalam Dunia Bisnis - Fatimah Annisa Azzahra; Indah Wardani; Lisa Nur Rizki Wulandari (Journal of Management and Creative Business, 2023)
Risk is part of the working life of individuals, groups, and institutions. In principle commercial or business activities are inseparable from risk management activities. In general, the term political risk then developed into a sovereign risk component that translates to the ability and will to fulfill government's financial obligations. At the same time, it should also be noted that present land risks are largely associated with broader risks that include operational risks other than financial risks. State risks combine the economic and financial indicators of a system with broad political and social characteristics and try to predict the conditions in which foreign investors will face the problems in relevant domestic environments. Beck describes the risk as physical damage caused by technology and the various forms of social, political, and communication